OmpR Indirectly Regulates Biosynthesis of Xenocoumacin 1 in Xenorhabdus nematophila - Yunfei Han; Xintong Zhao; Mengru He; Shujing Zhang; Gaijuan Tang; Yonghong Wang (Microorganisms)
Xenorhabdus nematophila has excellent potential for application in both medicine and agriculture due to its various active secondary metabolites. The transcriptional regulator OmpR negatively regulates Xenocoumacin 1 (Xcn1), which has wide antimicrobial activity. Here, we expressed and purified OmpR and verified its binding activities to promoters via an electrophoretic mobility shift assay. RNA sequencing was used to analyze the relevance and difference of differentially expressed genes between X. nematophila and its mutant ΔompR. Compared with the WT, 1127 differentially expressed genes were found in ΔompR, while 4150 co-expressed genes were detected. RT-qPCR data validated the RNA-seq results with 20 randomly selected genes. OmpR positively regulates the process of porphyrin metabolism, quorum sensing, β-Lactam resistance and glyoxylate and dicarboxylate metabolism, while negatively regulating the phosphotransferase system, two-component system and bacterial chemotaxis. OmpR indirectly regulates the biosynthesis of Xcn1 by positively regulating the process of glyoxylate metabolism, which consumes energy and precursors, and negatively regulates biomacromolecules biosynthesis, which provides energy and precursors. Overall, this work revealed the indirect effects of OmpR on the biosynthesis of Xcn1, serving as a foundation for future research into the intricate regulatory network of X. nematophila.